2006
DOI: 10.1038/sj.bjc.6603118
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of vinflunine in bladder cancer patients progressing after first-line platinum-containing regimen

Abstract: A multicentre phase II trial to determine the efficacy of vinflunine as second-line therapy in patients with advanced transitional cell carcinoma (TCC) of the bladder; secondary objectives were to assess duration of response, progression-free survival (PFS) and overall survival (OS), and to evaluate the toxicity associated with this treatment. Patients had tumours that failed or progressed after first-line platinum-containing regimens for advanced or metastatic disease, or had progressive disease after platinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
0
3

Year Published

2007
2007
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(109 citation statements)
references
References 28 publications
4
102
0
3
Order By: Relevance
“…The RR defined by the IRRC was similar to the estimate identified at study design, and confirmed the RR previously obtained with singleagent vinflunine in this patient population. 12 Responses were observed in all subsets of patients, including those with poor prognostic factors (visceral disease and decreased KPS) or with unfavorable characteristics (renal impairment, advanced age, and refractory disease defined as disease recurring <3 months after last prior therapy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RR defined by the IRRC was similar to the estimate identified at study design, and confirmed the RR previously obtained with singleagent vinflunine in this patient population. 12 Responses were observed in all subsets of patients, including those with poor prognostic factors (visceral disease and decreased KPS) or with unfavorable characteristics (renal impairment, advanced age, and refractory disease defined as disease recurring <3 months after last prior therapy).…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this trial was to confirm the activity of vinflunine demonstrated in the smaller phase 2 trial, 12 and to define the objective RR with more precision. The primary hypothesis of the trial was that vinflunine would result in a RR of approximately 15%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinflunine-related adverse events were not cumulative and included mostly grade 3-4 neutropenia, fatigue, and constipation (69,71).…”
Section: Vinca Alkaloids Vinfluninementioning
confidence: 99%
“…Recently completed clinical trials showed the activity of vinflunine in patients with advanced transitional cell carcinoma of the urothelium (TCCU; refs. 69,70), breast (71), NSCLC (72), and malignant pleural mesothelioma (73). In a recently reported phase 3 trial, the efficacy of vinflunine was equivalent to docetaxel in pretreated patients with NSCLC (74).…”
Section: Vinca Alkaloids Vinfluninementioning
confidence: 99%